Analisis Determinan Kelancaran Pengembalian Pembiayaan Murabahah BPRS Lantabur Tebuireng Lamongan: Pendekatan Regresi Linear Berganda - Afiza Ridha Zamzima; Dahruji, Dahruji; Taufiqur Rahman (Al-Buhuts, 2024)
This study aims to identify several factors that influence the smooth return of murabahah financing to MSME customers with the research object at BPRS Lantabur Tebuireng Lamongan. This type of research data data was obtained from primary and secondary data. The method used is quantitative research with sample data processing techniques using multiple linear regression analysis. The sampling technique was carried out using purposive sampling and a research sample of 67 MSME customers who were still active until the end of 2023 was obtained. From the research results it was found that the variables age, level of education, number of family dependents, business turnover, and religiosity simultaneously influence the smooth return of murabahah financing as indicated by a significance value 0,000. Meanwhile, partial test results show that the factors that have a significant influence on the level of smooth returns on murabahah financing for MSME customers are age, business turnover, and religiosity